Guest

Two of the lines represented by the equation ay4 + bxy3 + cx2y2 + dx3y + ex4 = 0 will be perpendicular, then A. (b + d)(ad + be) + (e - a)2(a + c + e) = 0 B. (b + d)(ad + be) + (e + a)2(a + c + e) = 0 C. (b - d)(ad - be) + (e - a)2(a + c + e) = 0 D. (b - d)(ad - be) + (e + a)2(a + c + e) = 0

Two of the lines represented by the equation ay4 + bxy3 + cx2y2 + dx3y + ex4 = 0 will be perpendicular, then
A. (b + d)(ad + be) + (e - a)2(a + c + e) = 0
B. (b + d)(ad + be) + (e + a)2(a + c + e) = 0
C. (b - d)(ad - be) + (e - a)2(a + c + e) = 0
D. (b - d)(ad - be) + (e + a)2(a + c + e) = 0

Grade:

2 Answers

Saurabh Koranglekar
askIITians Faculty 10336 Points
2 years ago
Dear student

Please attach the image of the question

Regards
Vikas TU
14149 Points
2 years ago
Dear student 
Question is not clear 
Please attach an image, 
We will happy to  help you 
Good Luck
Cheers

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free